Supramolecular magnetogels as nanocarriers for multimodal cancer therapy - Veloso, Sérgio Rafael Silva (2019)
Superparamagnetic manganese ferrite (MnFe2O4) nanoparticles were successfully incorporated into self-assembled peptide-derived hydrogels. The magnetogels were evaluated as drug nanocarriers through fluorescence-based techniques (fluorescence emission, FRET and fluorescence anisotropy).